Pasiyam sa sineng pambansa. IN On the “end” of national cinema in the Philippines - a roundtable discussion [column] - Cordero, Kristian S. (2017)
Access online through this link: https://www.plarideljournal.org/article/pasiyam-sa-sineng-pambansa
Keywords: Motion picture industry; Literary criticism